2022
DOI: 10.2147/jir.s362066
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin BacSp222 and Its Succinylated Forms Exhibit Proinflammatory Activities Toward Innate Immune Cells 

Abstract: Purpose The zoonotic opportunistic pathogen Staphylococcus pseudintermedius 222 produces BacSp222 – an atypical peptide exhibiting the features of a bacteriocin, a virulence factor, and a molecule modulating the host inflammatory reaction. The peptide is secreted in an unmodified form and, additionally, two forms modified posttranslationally by succinylation. This study is a comprehensive report focusing on the proinflammatory properties of such molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 77 publications
(99 reference statements)
3
20
0
Order By: Relevance
“…BacSp222 bacteriocin, its succinylated form (suc-K20-BacSp222), as well as bacteriocin deprived of Nterminal formyl-methionine (-fM-BacSp222) were obtained and analyzed strictly as described in our previous work [15]. As is presented in the above-cited study, the purity (over 99%), homogeneity, and identity of the peptides were checked by an analytical reversed-phase high-pressure liquid chromatography (RP-HPLC) and mass spectrometry.…”
Section: Peptides and Protein Chemistry Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…BacSp222 bacteriocin, its succinylated form (suc-K20-BacSp222), as well as bacteriocin deprived of Nterminal formyl-methionine (-fM-BacSp222) were obtained and analyzed strictly as described in our previous work [15]. As is presented in the above-cited study, the purity (over 99%), homogeneity, and identity of the peptides were checked by an analytical reversed-phase high-pressure liquid chromatography (RP-HPLC) and mass spectrometry.…”
Section: Peptides and Protein Chemistry Techniquesmentioning
confidence: 99%
“…As we have shown above, all tested forms of BacSp222 bacteriocin were able to activate the human TLR2 receptor. Since our previously published results demonstrated that BacSp222 induced TNF expression in murine macrophage-like cell line [15], we have decided to verify if TLR2 antagonists, such as sparstolonin B or TL2-C29 [22,23], affect the TNF production by bacteriocin-stimulated RAW 264.7 and P388.D1 cells. The cells were pre-treated with mentioned antagonists for 30 minutes and then stimulated for 6 hours with speci c BacSp222 bacteriocin or LTA (the ligand for TLR2 and a positive control of the test).…”
Section: Tlr2 Antagonists Inhibit Tnf Release By Bacteriocinstimulate...mentioning
confidence: 99%
See 3 more Smart Citations